2023
DOI: 10.1186/s12877-023-04088-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of young-old and old-old people using functional evaluation, gait characteristics, and cardiopulmonary metabolic energy consumption

Abstract: Background Walking is an important factor in daily life. Among older adults, gait function declines with age. In contrast to the many studies revealing gait differences between young adults and older adults, few studies have further divided older adults into groups. The purpose of this study was to subdivide an older adult population by age to identify age-related differences in functional evaluation, gait characteristics and cardiopulmonary metabolic energy consumption while walking. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Some authors 1,3,4) concur with this age limit; others have reported a cutoff of 75 years. [5][6][7][8] This observation is clinically significant. The difficulty of treating older individuals as a homog-enous group is reflected in the Australian clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors 1,3,4) concur with this age limit; others have reported a cutoff of 75 years. [5][6][7][8] This observation is clinically significant. The difficulty of treating older individuals as a homog-enous group is reflected in the Australian clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have suggested that the 65–74 and ≥75 years of age groups differ in mental and physical health. 6 , 7 ) The analysis of the surveys in these previous studies, initially divided the participants into age groups to explore age-related differences. In contrast, based on similarities in disease profiles and using clustering techniques, Geifman et al 8 ) investigated the feasibility of redefining age ranges and concluded that the 76–98 years of age group was distinct in terms of age-related diseases including Alzheimer disease, dementia, cataracts, and Parkinson disease.…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel study that involves a comparison of gait stability between the young and elderly populations in their habitual walking speed using the ZMP method. Most previous studies for understanding gait stability in the elderly focused on gait characteristics, such as walking speed, stride length, and the time for double-limb support [31]. In this study, the dynamic stability of habitual walking was assessed to investigate the gait of the elderly compared to the young.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2017 National Survey of Older Koreans, the proportions of older adults aged 65−74 and over 75 years were reported to be about 57% and 43%, respectively; the proportion of those aged 75 years or more has been confirmed to be increasing continuously [ 31 ]. In addition, recent nutrition related studies have reported comparable clinical outcomes for groups classified into 65–74 years (young-old) and 75 or older (old-old) [ 32 33 ]. Therefore, in this study, based on age, participants were categorized into 2 groups: 1) 65−74 years old and 2) ≥ 75 years old.…”
Section: Methodsmentioning
confidence: 99%